2020 IEEE Frontiers in Education Conference (FIE) 2020
DOI: 10.1109/fie44824.2020.9274201
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluate the Factors for Flipped Classrooms for Data Management Courses

Abstract: This Research to Practice Full Paper presents a framework to evaluate and design flipped classroom activities for data science and management courses. Variants of flipped classrooms have been employed in STEM fields with great success in students' learning outcomes. Research shows that flipped classrooms would improve students' learning if it is implemented following rigorous procedures of an efficient instructional design. As a result, one of the critical focus of current flipped classroom research is what fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Hence, assessing BRDM's results is based not only on the feedback and self-rating of the participants' competencies with further learning needs (typical measures of success in many previous trainings) but the returned DMPs. Fourth, a flipped classroom approach that is rarely used as a teaching method in previous RDM training (Griffin, 2020;Johnston & Jeffryes, 2015;Mithun & Luo, 2020), was adapted in the BRDM 2021 course. Fifth, many previous RDM trainings have been criticised for inadequate reporting (Goben & Griffin, 2019;Perrier et al, 2017).…”
Section: The Value Of Brdm and Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, assessing BRDM's results is based not only on the feedback and self-rating of the participants' competencies with further learning needs (typical measures of success in many previous trainings) but the returned DMPs. Fourth, a flipped classroom approach that is rarely used as a teaching method in previous RDM training (Griffin, 2020;Johnston & Jeffryes, 2015;Mithun & Luo, 2020), was adapted in the BRDM 2021 course. Fifth, many previous RDM trainings have been criticised for inadequate reporting (Goben & Griffin, 2019;Perrier et al, 2017).…”
Section: The Value Of Brdm and Lessons Learnedmentioning
confidence: 99%
“…Though planning and implementing the flipped classroom approach takes a lot of work from teachers, it pays back by increasing flexibility and helping activate participants. Still, quizzes or follow-up tasks are essential to show that participants learned the pre-class materials, as Mithun and Luo (2020) have pointed out.…”
Section: The Value Of Brdm and Lessons Learnedmentioning
confidence: 99%
“…While our literature review shows that innovative teaching methods such as flipped classrooms might improve student learning outcomes and teacher satisfaction, researchers have found that the success of flipped implementations depends on the content area, instructional design, and level of student expertise (e.g., Mithun & Luo, 2020). One common obstacle in using these approaches is the handling of students skipping video lectures due to a lack of motivation; this lack of engagement often leads to overwhelming feelings when they cannot follow the course content (Sobral, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Emerging fields such as Big Data and Data Science require new IT graduates to demonstrate their mastery in data acquisition, data management, and data inference skills when they enter the workforce (Mithun & Luo, 2020). Thus, introductory programming courses such as database programming and design represent crucial milestones in IT education, as they reflect students' ability to solve problems and design appropriate solutions (Skala & Drilk, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation